GOD AS CREATOR: KONSEP PENCIPTAAN ALAM SEMESTA BERDASARKAN KITAB KEJADIAN PASAL 1-2 - Ririn Valentina Halawa (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2022)
God said that the creation of the universe must be complete, as stated in Genesis 1-2. This article is the result of thought and analysis of the creation of the universe. Atheists who do not know God believe that the universe's existence had no beginning. However, Christians believe that the universe exists because of the Creator. The article's purpose is to explain the concept of the creation of the universe based on the Book of Genesis and answer questions about the Creator of the earth. The universe exists because there is a Creator. In this case, Allah states that the world was created in six days. The reality of God's activity and the Word of God cannot be denied as the glory of God who created the universe, namely the heavens and the earth, ex nihilo. Creationism is the foundation of Christianity, as evidenced by the powerful authority of God's Word. Genesis 1-2 describes arguments against and refutation of Science's claims and philosophical views that contradict the validity of the Bible. Thus the existence of the world is because of the Creator. This article shows that God is the Creator of the universe, so the universe exists.